Pandangan Para Ulama Tentang Darah Haid dan Darah Istihadhah - Rayyan Ulya Amani; Suyudi Arif; Kholil M. Nawawi (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Understanding the law of blood that comes out of a woman's vagina is very important, because it will affect the activities of worship, mu'amalah, and munakahat. If a woman can distinguish the blood that comes out, it will be easy for her to experience it. When a woman confused by the blood. In contrast to women who can not distinguish the blood that comes out and also forgets the habits that happened to her, then many questions and doubts will arise about the blood that comes out of her vagina. In this case, the main problem and purpose of the study is how the views of the Four Imams of the School on menstrual blood and blood istihadhah also similarities and differences of opinion on menstrual blood and blood istihadhah. This thesis uses a type of qualitative research, where this research does not use numbers as data. The method of data analysis used is descriptive content analysis, explaining and providing a broad and in -depth picture of the views of the four Imams of the School on menstrual blood and istihadhah blood. As primary data are Kitab Madzahibul Arba'ah and Kitab Bidayatul Mujtahid. While the secondary data used is other literature relevant to the title of this script. About data collection techniques is to use library research techniques. So the result of this study is that the four Imams of the Madhhab agree that menstruating women are women who are prevented from performing some acts of worship, but this does not apply to istihadhah women. There are similarities and differences of opinion of the four Imams of the Madhhab regarding menstrual blood and istihadhah blood. Like the early age and menopause, the minimum and maximum time of menstruation, the color and nature of the blood, an-naqa ', and the sacred signs of menstruation for women who experience it. Keywords: Imam, Menstruation, Istihadhah